Innovative deep eutectic solvent approach vs. conventional alkaline for kenaf seed protein extraction: a comprehensive comparison of structural, thermal, nutritional and techno-functional properties - Arulrajah, Brisha; Qoms, Mohammed S.; Wan Ibadullah, Wan Zunairah; Saari, Nazamid (Elsevier Ltd, 2025)
This study was the first to compare the effects of innovative deep eutectic solvent-based green extractant (ChCl:U and ChCl:Gly) and conventional alkaline solubilisation-acid precipitation (CA) approaches on kenaf seed protein extractability, structural, thermal, nutritional and techno-functional properties. Both CA and ChCl:U methods showed better protein extractability than ChCl:Gly. DES-based extraction induced lesser structural changes in kenaf seed protein compared to CA method. All proteins displayed high digestibility, but DES extraction produced more balanced amino acid ratios. Both CA and ChCl:U methods exhibited superior functional performance at all the tested pH compared to ChCl:Gly. Notably, CA demonstrated superior emulsification properties, whereas ChCl:U exhibited the highest foaming properties. The emulsification and foaming activities with all extraction methods were the highest in alkaline conditions, while better stabilities were observed in acidic conditions. Overall, the DES protein extraction method using ChCl:U can be employed as green alternative for extracting kenaf seed protein.